Air purification material and preparation method thereof

By combining diatomaceous earth, TiO2, MnO2, WO3 in the air purification material, the problem of high light wavelength requirements of photocatalytic method is solved, efficient VOC removal under different lighting conditions is achieved, and adsorption processing efficiency is improved.

CN115888636BActive Publication Date: 2024-12-20SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310012537.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-05
Publication Date
2024-12-20
Estimated Expiration
2043-01-05

AI Technical Summary

Technical Problem

A single photocatalytic method has high requirements for light wavelength, which affects the efficiency of removing volatile organic compounds (VOCs).

Method used

An air purification material, including diatomaceous earth, TiO2, MnO2, WO3, is prepared by diatomaceous earth as a support to support metal catalyst and composite semiconductor, combined with physical adsorption method and chemical photocatalytic method, adjusting pH value and ultrasonic dispersion, etc. , improve the adsorption treatment efficiency of VOC.

Benefits of technology

The adsorption processing efficiency of VOC is significantly improved under sunlight and dark conditions, the photocatalytic efficiency is enhanced, and the volatile organic compounds are effectively removed under different light conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005128351430000051
    Figure GDA0005128351430000051
  • Figure GDA0005128351430000061
    Figure GDA0005128351430000061
  • Figure GDA0005128351430000101
    Figure GDA0005128351430000101
Patent Text Reader

Abstract

The present invention discloses an air purification material and a preparation method thereof. The air purification material comprises: diatomite, TiO2, MnO2, WO3, wherein the amount ratio of the TiO2, the MnO2 and the WO3 is (1-5):(1-5):(1-5); the preparation method of the air purification material comprises: 1) grinding, pickling, calcining and hydrophobic modification of the diatomite to obtain the pretreated diatomite; 2) preparing sol A and solution B, mixing the sol A with the solution B to prepare a sol, aging, drying and grinding to obtain a diatomite / TiO2 / MnO2 composite powder; 3) mixing the diatomite / TiO2 / MnO2 composite powder, WO3 and a complexing agent, then adjusting the pH value, ultrasonically dispersing for the first time, drying, grinding, calcining and ultrasonically dispersing for the second time to obtain a diatomite / TiO2 / MnO2 / WO3 composite powder. The air purification material provided by the present invention can efficiently remove volatile organic compounds in the air.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of air purification, and in particular to an air purification material and a preparation method thereof. Background Art

[0002] At present, the more commonly used methods for treating VOCs (Volatile Organic Compounds) are material adsorption and photocatalysis. The material adsorption method cannot completely remove VOCs, and the adsorption efficiency is easily affected by environmental factors. The photocatalytic method mainly involves the catalyst generating strongly oxidizing hydroxyl radicals under light. The free radicals oxidize the VOCs adsorbed on the catalyst surface and decompose them into water and carbon dioxide. The whole process has low energy consumption and relatively mild reaction conditions.

[0003] However, the single photocatalytic method has high requirements on the light wavelength, which affects the efficiency of VOC removal. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the present invention proposes an air purification material and a preparation method thereof, aiming to solve the problem that the current single photocatalytic method has high requirements on the wavelength of light, which affects the efficiency of removing VOCs.

[0005] To achieve the above-mentioned purpose, the present invention proposes an air purification material, characterized in that it includes: diatomaceous earth, TiO2, MnO2, WO3, and the amount ratio of the TiO2, the MnO2 and the WO3 is (1-5):(1-5):(1-5).

[0006] Optionally, the amount ratio of the TiO2, the MnO2 and the WO3 is 1:1:1.

[0007] To achieve the above-mentioned purpose, the present invention also proposes a method for preparing an air purification material, comprising the following steps: 1) grinding, pickling, calcining and hydrophobically modifying diatomaceous earth to obtain pretreated diatomaceous earth; 2) preparing sol A and solution B, mixing the sol A with the solution B to form a sol, and aging, drying and grinding to obtain a diatomaceous earth / TiO2 / MnO2 composite powder; wherein the sol A includes an organic manganese salt and a first complexing agent, and the solution B includes the pretreated diatomaceous earth and tetrabutyl titanate; 3) mixing the diatomaceous earth / TiO2 / MnO2 composite powder, WO3 and a second complexing agent, and then adjusting the pH value, ultrasonically dispersing for the first time, drying, grinding, calcining and ultrasonically dispersing for the second time to obtain a diatomaceous earth / TiO2 / MnO2 / WO3 composite powder.

[0008] Optionally, in step 1), the acid concentration of the pickling is 45%-65%, and the pickling time is 4-6 hours; and / or, the calcination temperature is 400-550° C., and the calcination time is 1-4 hours.

[0009] Optionally, in step 1), the hydrophobic modification comprises adding a hydrophobic modifier and performing the hydrophobic modification by a low-temperature reflux method, wherein the hydrophobic modifier comprises at least one of APTES, PTES or γ-MPS.

[0010] Optionally, in step 1), the reflux temperature is 75-85° C.; and / or the reflux time is 9-12 h.

[0011] Optionally, in step 2), the mass ratio of the organic manganese salt to the complexing agent is 2:(3-3.5).

[0012] Optionally, the volume ratio of the sol A and the solution B is 1:(4-4.5).

[0013] Optionally, in step 2), the aging time is greater than or equal to 24 hours; and / or, the drying temperature is 80-110° C., and the drying time is 8-12 hours.

[0014] Optionally, in step 3), the calcination temperature is 400-500° C., and the calcination time is greater than 2 hours.

[0015] In order to achieve the above object, the present invention also provides an air purification material prepared by the above preparation method.

[0016] Beneficial effects of the invention: The invention provides an air purification material, the preparation method of which combines physical adsorption with chemical photocatalysis, using diatomite as a carrier to load metal catalysts and composite semiconductors. The metal catalyst is conducive to the migration of photogenerated electrons to the outside, effectively preventing the simple recombination of electron holes, and the energy difference between the two semiconductors in the composite semiconductor can effectively separate the charges, thereby improving the quantum efficiency. They are combined with the adsorption capacity of diatomite to greatly improve the adsorption and treatment efficiency of VOCs under sunlight and dark conditions. DETAILED DESCRIPTION

[0017] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0018] Unless defined otherwise, all technical and scientific terms used herein have the common meaning in the art to which the claimed subject matter belongs.

[0019] At present, the more commonly used methods for treating VOCs (Volatile Organic Compounds) are material adsorption and photocatalysis. The material adsorption method cannot completely remove VOCs, and the adsorption efficiency is easily affected by environmental factors. The photocatalytic method mainly involves the catalyst generating strongly oxidizing hydroxyl radicals under light. The free radicals oxidize the VOCs adsorbed on the catalyst surface and decompose them into water and carbon dioxide. The whole process has low energy consumption and relatively mild reaction conditions.

[0020] However, the single photocatalytic method has high requirements on the light wavelength, which affects the efficiency of VOC removal.

[0021] To solve the above problems, the present invention proposes an air purification material, characterized in that it includes: diatomaceous earth, TiO2, MnO2, WO3, and the amount ratio of the TiO2, the MnO2 and the WO3 is (1-5): (1-5): (1-5). In a specific embodiment of the present invention, diatomaceous earth is used as a carrier, a manganese metal catalyst is loaded, and a TiO2 / WO3 composite semiconductor material is loaded. The above active ingredients are compounded in a ratio of (1-5): (1-5): (1-5), which greatly improves the synergistic effect of the components in the air purification material and improves the adsorption and treatment efficiency of VOCs in the air purification material under sunlight and dark conditions.

[0022] Furthermore, the molar ratio of the TiO2, MnO2 and WO3 is 1:1:1. When TiO2, MnO2 and WO3 are compounded in a ratio of 1:1:1, the four materials including diatomite can have a good synergistic effect to the greatest extent, activate the active sites, and make the active components dispersed evenly in the diatomite, so as to improve the photocatalytic efficiency.

[0023] The preparation method of the air purification material comprises the following steps: 1) grinding, acid washing, calcining and hydrophobic modification of diatomaceous earth to obtain pretreated diatomaceous earth;

[0024] The purpose of the pretreatment is to remove the impurities contained in diatomite, and to increase the specific surface area by burning treatment, while removing the organic matter on the surface, and then hydrophobically modifying it. After grinding the diatomite with a ball mill, the particle size of the diatomite can be made uniform, and the micropores can be exposed, which is more conducive to the adsorption of VOCs. After acid treatment and high-temperature calcination, impurities can be reduced and the specific surface area can be increased to increase the loading amount of the catalyst. The more hydroxyl groups on the surface of diatomite, the better the adsorption performance. Since the hydroxyl groups on the surface of diatomite have strong hydrophilicity, the adsorption amount of VOCs will be reduced, so after hydrophobic modification, the adsorption effect of diatomite on VOCs can be improved.

[0025] Furthermore, in step 1), the acid concentration of the pickling is 45%-65%, and the pickling time is 4-6 hours; and / or, the calcination temperature is 400-550° C., and the calcination time is 1-4 hours.

[0026] In one embodiment of the present invention, the acid used for pickling is sulfuric acid. Pickling diatomite is to use sulfuric acid, nitric acid, etc. as leaching agents to remove impurity minerals in crude diatomite and dredge the pores to purify the diatomite. Unreasonable acid concentration and pickling time will affect the purification effect of diatomite. Calcination can remove organic impurities more thoroughly, and at the same time can retain the integrity of most of the pores of diatomite and good adsorption. If the temperature is too high, the microporous structure of the diatom body will be completely destroyed, part of the pore wall will crystallize and melt, and the porous structure of the diatomite will be pierced, resulting in reduced adsorption.

[0027] Further, in step 1), the hydrophobic modification includes adding a hydrophobic modifier and performing hydrophobic modification by a low temperature reflux method, wherein the hydrophobic modifier includes at least one of APTES, PTES or γ-MPS. Wherein, APTES is γ-aminopropyltriethoxysilane, PTES is heptadecafluorodecyltriethoxysilane, γ-MPS is γ-methacryloxypropyltrimethoxysilane, and the mass ratio of the hydrophobic modifier to diatomaceous earth is 1:2.

[0028] Furthermore, the reflux temperature is 75-85° C. and / or the reflux time is 9-12 hours. The low-temperature reflux method is used to allow the hydrophobic modifier to fully react with the diatomaceous earth.

[0029] 2) preparing sol A and solution B, mixing the sol A and solution B to form a sol, and aging, drying, and grinding to obtain a diatomite / TiO2 / MnO2 composite powder; wherein the sol A includes an organic manganese salt and a first complexing agent, and the solution B includes the pretreated diatomite and tetrabutyl titanate;

[0030] In one embodiment of the present invention, the first complexing agent is citric acid, and the specific operation includes: adding manganese acetate and citric acid to distilled water, wherein the mass ratio of manganese acetate to citric acid is 2:3, stirring until completely dissolved, adjusting the solution pH to 6 with concentrated ammonia water, stirring and mixing evenly, and obtaining solution A. Raising the solution temperature to 80°C, and after the solution is in a gel state, obtaining sol A. Dissolving diatomite in anhydrous ethanol solvent, stirring for a period of time to make it evenly mixed, slowly adding tetrabutyl titanate, using ultrasonic dispersion for 30 minutes, forming solution B; mixing sol A and solution B, stirring evenly after mixing, raising the solution to 80°C, and dripping nitric acid and deionized water into the mixed solution, stirring while dripping, stopping stirring after the solution gradually forms a gel, standing and aging at room temperature for 24 hours, drying at a constant temperature in an oven, taking out, grinding the sample, and obtaining diatomite / TiO2 / MnO2 composite powder.

[0031] Further, the mass ratio of the organic manganese salt to the complexing agent is 2:(3-3.5); and / or, the volume ratio of the sol A and the solution B is 1:(4-4.5). In a specific embodiment of the present invention, the mass ratio of the organic manganese salt to the complexing agent is 2:3, and the volume ratio of the sol A and the solution B is 1:4.2. The mixing and stirring are carried out according to the above material ratio parameters, so that the various substances in the sol-gel method are evenly dispersed, the colloid is excellent, and it is conducive to continue to react with WO3.

[0032] Furthermore, the aging time is greater than or equal to 24 hours; and / or, the drying temperature is 80-110°C, and the drying time is 8-12 hours. In a specific embodiment of the present invention, the aging time at room temperature is 24 hours, and then the aging time is constant-temperature dried in an oven at 80-110°C for 8-12 hours. The aging time and drying time make the obtained diatomite / TiO2 / MnO2 composite powder fine, which is conducive to improving the treatment efficiency of VOC.

[0033] 3) mixing the diatomite / TiO2 / MnO2 composite powder, WO3 and a second complexing agent, then adjusting the pH value, performing a first ultrasonic dispersion, drying, grinding, calcining, and a second ultrasonic dispersion to obtain a diatomite / TiO2 / MnO2 / WO3 composite powder.

[0034] In a specific embodiment of the present invention, the diatomite / TiO2 / MnO2 composite powder and WO3 powder obtained in the above steps are added to 200mL distilled water in a ratio of nTiO2 / nMnO2 / nWO3=1:1:1 and dispersed and stirred evenly. Then, citric acid (second complexing agent) of the same mass as the composite powder is added, and the pH is adjusted to between 5 and 6 with ammonia water, and ultrasonically dispersed for 2h. After drying in an oven at 80°C, grind evenly, and finally place in a muffle furnace for calcination at 400-500°C for 2h, and then put into an ultrasonic disperser for oscillation for 30min, stir evenly, and the diatomite / TiO2 / MnO2 / WO3 composite powder can be obtained.

[0035] Furthermore, the calcination temperature is 400-500°C, and the calcination time is greater than 2 hours. TiO2 is combined with the diatomite carrier in the form of Ti-O-Si. As the calcination temperature increases, the TiO2 loaded on the surface of the diatomite gradually changes from amorphous to anatase, and at the same time, the grain size increases, and the catalytic activity increases.

[0036] To solve the above problems, the present invention also proposes an air purification material prepared by the above preparation method. The air purification material can be efficiently applied to the field of physical and chemical adsorption of volatile organic compounds with boiling points between 50°C and 260°C in the air, such as removing benzene, polycyclic aromatic hydrocarbons, aromatic amines, resin compounds, aldehydes and nitrosamines in the atmosphere.

[0037] The experimental materials used in the embodiments of the present invention include:

[0038]

[0039]

[0040] Example 1: Preparation of diatomite / TiO2 / MnO2 / WO3 composite material

[0041] Hydrophobic modification of diatomite: Grind the diatomite with a ball mill at a speed of 100r / min for 3h; then pickle it in a 45% sulfuric acid solution for 6h; and then calcine it at 400℃ for 4h. Take 10g of calcined and ground sieved diatomite and disperse it in 80mL of dry toluene solution. After sufficient dispersion, add the hydrophobic modifier APTES from one end of the three-necked flask to the diatomite / toluene mixture under constant temperature stirring and reflux, wherein the mass ratio of the hydrophobic modifier to the diatomite is 1:2. Stir the mixture at 75℃ (300rpm) and reflux for 12h. After the silanization reaction, centrifuge and filter the product, wash it with ethanol three times (to remove the solvent and excess unreacted silane coupling agent), and dry it at 60℃ for 12h to obtain hydrophobically modified diatomite.

[0042] Preparation of diatomite / TiO2 / MnO2 composite powder: Weigh 1.8g of manganese acetate and 2.5g of citric acid (m manganese acetate: m citric acid = 2:3) and add them to 20mL of distilled water. Stir thoroughly until completely dissolved, adjust the solution pH to 6 with concentrated ammonia water, stir thoroughly and mix well to obtain solution A. Raise the temperature of solution A to 80°C, and after the solution is in a gel state, obtain sol A. Dissolve 10g of hydrophobically modified diatomite in 200ml of anhydrous ethanol solvent, stir well, slowly add 3.3ml of tetrabutyl titanate, and use ultrasonic dispersion for 30min to form solution B. Sol A and solution B are mixed and stirred evenly after mixing. The temperature of the solution is raised to 80°C, and nitric acid and deionized water are added dropwise to the mixed solution while stirring. After the solution gradually forms a gel, stirring is stopped, and the solution is allowed to stand and age for 24 hours at room temperature. The solution is dried at a constant temperature of 80°C in an oven for 12 hours. After taking out, the sample is ground to obtain diatomaceous earth / TiO2 / MnO2 composite powder.

[0043] Preparation of diatomite / TiO2 / MnO2 / WO3 composite powder: Disperse and stir the diatomite / TiO2 / MnO2 composite powder and WO3 powder (nTiO2 / nMnO2 / nWO3=1:1:1) obtained in the above steps with 200mL of distilled water. Add citric acid (complexing agent) of the same mass as the composite powder, adjust the pH to between 5 and 6 with ammonia water, and disperse ultrasonically for 2h. After drying in an oven at 80℃, grind evenly, and finally place in a muffle furnace and calcine at 400℃ for 2h, then put into an ultrasonic disperser for oscillation for 30min, stir evenly, and obtain diatomite / TiO2 / MnO2 / WO3 composite powder.

[0044] Example 2: Preparation of diatomite / TiO2 / MnO2 / WO3 composite material

[0045] Hydrophobic modification of diatomite: Grind the diatomite with a ball mill at a speed of 300r / min for 1h; then pickle it in a 65% sulfuric acid solution for 4h; and then calcine it at 550℃ for 1h. Take 10g of calcined and ground sieved diatomite and disperse it in 80mL of dry toluene solution. After sufficient dispersion, add hydrophobic modifier PTES from one end of the three-necked flask to the diatomite / toluene mixture during constant temperature stirring and reflux, wherein the mass ratio of hydrophobic modifier to diatomite is 1:2. Stir the mixture at 85℃ (500rpm) and reflux for 9h. After the silanization reaction, centrifuge and filter the product, wash it with ethanol three times (to remove the solvent and excess unreacted silane coupling agent), and dry it at 80℃ for 8h. Hydrophobically modified diatomite can be obtained.

[0046] Preparation of diatomite / TiO2 / MnO2 composite powder: Weigh 1.8g of manganese acetate and 3.3g of citric acid (m manganese acetate: m citric acid = 2:3.5) and add them to 20mL of distilled water. Stir thoroughly until completely dissolved, adjust the solution pH to 6 with concentrated ammonia water, stir thoroughly and mix well to obtain solution A. Raise the temperature of solution A to 80°C, and after the solution is in a gel state, obtain sol A. Dissolve 10g of hydrophobically modified diatomite in 200ml of anhydrous ethanol solvent, stir well, slowly add 3.3ml of tetrabutyl titanate, and use ultrasonic dispersion for 30min to form solution B. Sol A and solution B are mixed and stirred evenly after mixing. The temperature of the solution is raised to 80°C, and nitric acid and deionized water are added dropwise to the mixed solution while stirring. After the solution gradually forms a gel, stirring is stopped, and the solution is allowed to stand and age for 24 hours at room temperature. The solution is dried at a constant temperature of 80°C in an oven for 12 hours. After taking out, the sample is ground to obtain diatomaceous earth / TiO2 / MnO2 composite powder.

[0047] Preparation of diatomite / TiO2 / MnO2 / WO3 composite powder: Disperse and stir the diatomite / TiO2 / MnO2 composite powder and WO3 powder (nTiO2 / nMnO2 / nWO3=1:1:1) obtained in the above steps with 200mL of distilled water. Add citric acid (complexing agent) of the same mass as the composite powder, adjust the pH to between 5 and 6 with ammonia water, and disperse ultrasonically for 2h. After drying in an oven at 80℃, grind evenly, and finally place in a muffle furnace and calcine at 500℃ for 2h, then put into an ultrasonic disperser for oscillation for 30min, stir evenly, and obtain diatomite / TiO2 / MnO2 / WO3 composite powder.

[0048] Example 3: Preparation of diatomite / TiO2 / MnO2 / WO3 composite material

[0049] Hydrophobic modification of diatomite: Grind the diatomite with a ball mill at a speed of 300r / min for 1h; then pickle it in a 65% sulfuric acid solution for 4h; and then calcine it at 550℃ for 1h. Take 10g of calcined and ground sieved diatomite and disperse it in 80mL of dry toluene solution. After sufficient dispersion, add the hydrophobic modifier γ-MPS from one end of the three-necked flask to the diatomite / toluene mixture under constant temperature stirring and reflux, wherein the mass ratio of the hydrophobic modifier to the diatomite is 1:2. Stir the mixture at 85℃ (500rpm) and reflux for 9h. After the silanization reaction, centrifuge and filter the product, wash it with ethanol three times (to remove the solvent and excess unreacted silane coupling agent), and dry it at 80℃ for 8h. Hydrophobically modified diatomite can be obtained.

[0050] Preparation of diatomite / TiO2 / MnO2 composite powder: Weigh 1.8g of manganese acetate and 3.3g of citric acid (m manganese acetate: m citric acid = 2:3.5) and add them to 45mL of distilled water. Stir thoroughly until completely dissolved, adjust the solution pH to 6 with concentrated ammonia water, stir thoroughly and mix well to obtain solution A. Raise the temperature of solution A to 80°C, and after the solution is in a gel state, obtain sol A. Dissolve 10g of hydrophobically modified diatomite in 200ml of anhydrous ethanol solvent, stir well, slowly add 3.3ml of tetrabutyl titanate, and use ultrasonic dispersion for 30min to form solution B. Sol A and solution B are mixed and stirred evenly after mixing. The temperature of the solution is raised to 80°C, and nitric acid and deionized water are added dropwise to the mixed solution while stirring. After the solution gradually forms a gel, stirring is stopped, and the solution is allowed to stand and age for 24 hours at room temperature. The solution is dried at a constant temperature of 80°C in an oven for 12 hours. After taking out, the sample is ground to obtain diatomaceous earth / TiO2 / MnO2 composite powder.

[0051] Preparation of diatomite / TiO2 / MnO2 / WO3 composite powder: Disperse and stir the diatomite / TiO2 / MnO2 composite powder and WO3 powder (nTiO2 / nMnO2 / nWO3=1:1:1) obtained in the above steps with 200mL of distilled water. Add citric acid (complexing agent) of the same mass as the composite powder, adjust the pH to between 5 and 6 with ammonia water, and disperse ultrasonically for 2h. After drying in an oven at 80℃, grind evenly, and finally place in a muffle furnace and calcine at 500℃ for 2h, then put into an ultrasonic disperser for oscillation for 30min, stir evenly, and obtain diatomite / TiO2 / MnO2 / WO3 composite powder.

[0052] Comparative Example 1: Untreated diatomaceous earth

[0053] Comparative Example 2: Preparation of pretreated diatomaceous earth

[0054] Grinding: Grind the diatomaceous earth in a ball mill at a speed of 200 r / min for 3 h;

[0055] Acid treatment: pickling in 45% sulfuric acid solution for 4h;

[0056] High temperature calcination treatment: calcination at 400-℃ for 2h to obtain purified diatomaceous earth.

[0057] Hydrophobic modification: 10g of ground and sieved diatomaceous earth was dispersed in 80mL of dry toluene solution. After sufficient dispersion, the hydrophobic modifier APTES was added dropwise from one end of the three-necked flask to the diatomaceous earth / toluene mixture under constant temperature stirring and reflux, wherein the mass ratio of the hydrophobic modifier to the diatomaceous earth was 2:1. The mixture was refluxed at 80°C and 300rpm for 9h. After the silanization reaction, the product was centrifuged and filtered, washed with ethanol three times, and dried at 70°C for 10h to obtain the pre-treated diatomaceous earth.

[0058] Comparative Example 3: Preparation of TiO2

[0059] In 50 ml of anhydrous ethanol solvent, add 10 ml of tetrabutyl titanate and stir evenly to form solution A; weigh 10 ml of hydrochloric acid, add 20 ml of deionized water to dilute, and mix after ultrasonication for 30 minutes to form solution B; then add solution B drop by drop into solution A at a rate of 4 to 5 seconds per drop. After the addition is completed, continue stirring for 30 minutes to form a sol. After standing for 12 hours, put it in an oven to dry and grind it into powder. Finally, calcine it in a muffle furnace at 550°C for 2 hours to obtain TiO2 powder.

[0060] Comparative Example 4: Preparation of TiO2 / MnO2 / WO3

[0061] Preparation of TiO2 / MnO2: Weigh 1.8g of manganese acetate and 2.5g of citric acid (m manganese acetate: m citric acid = 2:3) and add them to 20mL of distilled water. Stir thoroughly until completely dissolved, adjust the solution pH to 6 with concentrated ammonia water, stir thoroughly and mix well to obtain solution A. Raise the temperature of solution A to 80°C, and after the solution is in a gel state, obtain sol A; slowly add 3.3ml of tetrabutyl titanate to 60ml of anhydrous ethanol solvent, use ultrasonic dispersion for 30min to form solution B; mix sol A and solution B, stir well after mixing, raise the solution to 80°C, and drop nitric acid and deionized water into the mixed solution, stirring while dropping, stop stirring after the solution gradually forms a gel, let it stand for 24h at room temperature, dry it in an oven at 80-110°C at a constant temperature for 8-12 hours, take it out, grind the sample to obtain TiO2 / MnO2 composite powder.

[0062] Preparation of TiO2 / MnO2 / WO3:

[0063] The TiO2 / MnO2 composite powder and WO3 powder (TiO2 / MnO2 / WO3=1:1:1) obtained in the above steps are dispersed and stirred evenly with 200mL of distilled water. Add citric acid (complexing agent) of the same mass as the composite powder, adjust the pH to between 5 and 6 with ammonia water, and ultrasonically disperse for 2h. After drying in an oven at 80℃, grind evenly, and finally place in a muffle furnace for calcination at 400-500℃ for 2h, then put into an ultrasonic disperser for oscillation for 30min, stir evenly, and obtain TiO2 / MnO2 / WO3.

[0064] Comparative Example 5: Diatomaceous Earth Loaded TiO2

[0065] Disperse 10g of diatomaceous earth in 200ml of anhydrous ethanol solvent, add 10ml of tetrabutyl titanate, stir evenly to form solution A; weigh 10ml of hydrochloric acid, add 20ml of deionized water to dilute, and mix to form solution B after ultrasonic treatment for 30min; then add solution B drop by drop into solution A at a rate of 4 to 5 seconds per drop, and continue stirring for 30min after the addition is completed to form a sol. After standing for 12h, put it in an oven to dry and grind it into powder, and finally calcine it in a muffle furnace at 550℃ for 2h to obtain diatomaceous earth-loaded TiO2 material.

[0066] Further, the VOC treatment effect experiment was conducted on Example 1 and Comparative Examples 1-5. The specific operation was as follows: a certain mass (1 g) of VOC treatment material was weighed with a flat dish and placed in a self-made test device, the device included diatomite / TiO2 / MnO2 / WO3 air purification material, ultraviolet lamp, heating plate, circulation fan, VOC liquid inlet, internal gas sampling port, the temperature in the device was adjusted to 25°C, the humidity was 50%, and 100 μL of a mixed solution of volatile organic solvents (toluene, ethyl acetate, acetone, phenol mixed solution) (mass fraction 1.0%) was added to the heating plate through the injection port under ultraviolet light, natural light, and dark conditions, and then the test device was sealed, and the heating plate and fan were turned on to accelerate the volatilization of the VOC mixed solution and keep the gas concentration in the device uniform. After 5 hours, the concentration of the VOC mixed gas in the device reached equilibrium and stability, and the mass concentration of the VOC gas in the device was measured by sampling from the sampling port using an atmospheric sampler.

[0067] The calculation formula for the removal rate D of mixed organic solution is:

[0068] D=(C 空 -C t ) / C0×100%

[0069] Where: C0 is the initial mixed organic gas concentration; C t is the mass concentration of mixed organic gas at time t;

[0070] $C_{empty}$ is the mass concentration of the mixed organic gas at the blank test time $t$.

[0071] The test results are summarized in Table 1.

[0072] Table 1. Treatment effect experiments of Example 1 and Comparative Examples 1-5

[0073]

[0074]

[0075] Through the above treatment effect experiments, it can be intuitively shown that the air purification material provided by the present invention uses diatomite as a carrier, loads a metal catalyst and a composite semiconductor. The metal catalyst is beneficial to the migration of photo-generated electrons to the outside, effectively preventing the simple recombination of electron-hole pairs. The energy difference between the two semiconductors in the composite semiconductor can effectively separate charges, thereby improving the quantum efficiency. Combining their adsorption capacity with diatomite, compared with the untreated diatomite, pre-treated diatomite, $TiO_2$, $TiO_2 / MnO_2 / WO_3$, and diatomite-supported $TiO_2$ in Comparative Examples 1-5, it can greatly improve the adsorption treatment efficiency of VOCs under sunlight and dark conditions.

[0076] The above are only the preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention can have various changes and modifications. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.

Claims

1. An air purification material, characterized in that: The air purification material is used for purifying a mixture of toluene, ethyl acetate, acetone and phenol, and comprises diatomaceous earth, TiO2, MnO2 and WO3, wherein the amount ratio of the TiO2, the MnO2 and the WO3 is 1:1:1; The preparation method of the air purification material comprises the following steps: 1) Grinding, pickling, calcining and hydrophobically modifying diatomite to obtain pretreated diatomite; the mass concentration of the acid in the pickling is 45%-65%; the pickling time is 4-6h; the calcining temperature is 400-550°C; the calcining time is 1-4h; the hydrophobic modification includes: adding a hydrophobic modifier, the hydrophobic modifier includes at least one of γ-aminopropyltriethoxysilane, heptadecafluorodecyltriethoxysilane or γ-methacryloxypropyltrimethoxysilane, and the mass ratio of the hydrophobic modifier to the diatomite is 1:2; 2) preparing sol A and solution B, mixing the sol A and solution B to form a sol, aging, drying and grinding to obtain diatomite / TiO2 / MnO2 composite powder; comprising the following steps: adding manganese acetate and citric acid into distilled water, wherein the mass ratio of manganese acetate to citric acid is 2:3, stirring until completely dissolved, adjusting the solution pH to 6 with concentrated ammonia water, stirring and mixing until uniform, to obtain solution A; raising the temperature of solution A to 80°C, and obtaining sol A after the solution becomes gel-like; Dissolve diatomite in anhydrous ethanol solvent, stir for a period of time to make it evenly mixed, then slowly add tetrabutyl titanate, use ultrasonic dispersion for 30 minutes to form solution B; mix sol A and solution B, stir evenly after mixing, raise the solution temperature to 80°C, and drop nitric acid and deionized water into the mixed solution while stirring, stop stirring after the solution gradually forms a gel, let it stand at room temperature for 24 hours, dry it in an oven at a constant temperature, take it out, grind the sample, and obtain diatomite / TiO2 / MnO2 composite powder; 3) mixing the diatomite / TiO2 / MnO2 composite powder, WO3 and a second complexing agent, then adjusting the pH value to 5-6, performing a first ultrasonic dispersion, drying, grinding, calcining and a second ultrasonic dispersion to obtain a diatomite / TiO2 / MnO2 / WO3 composite powder; the calcination temperature is 400-500°C and the calcination time is greater than 2h.